Optimized Mn cycle enhanced synchronous removal of nitrate and antibiotics driven by manganese oxides/solid carbon composites: Microbiota assembly patterns and electron transport - Jia, Lixia; Qi Zhou; Wu, Weizhong (JOURNAL OF HAZARDOUS MATERIALS, 2025)
The reactive substance consisting manganese oxides (MnOx) and solid carbon have been reported to be effective in polishing secondary wastewater; however, the treatment characteristics and mechanism remains limited. In this study, MnOx/carbon (Mn-C) composites were applied in biofilters to evaluate simultaneous removal of nitrate and sulfamethoxazole (SMX), with the single carbon composites as control. Results showed that the effluent concentrations of NO3 –N and SMX were below 2.87 mg L- 1 and 7.97 mu g L- 1 under hydraulic retention time (HRT) of 6 h. The intermittent aeration optimized Mn cycle with treatment performance improved under lower HRT and Mn(II) accumulation decreased. Mn-C composites could reduce the emission of N2O, CO2 and CH4. The dominant genera gradually evolved from fermentation to glycogen aggregation, and from heterotrophic/sulfur autotrophic to heterotrophic denitrifiers by intracellular substance and manganese autotrophic/heterotrophic bacteria. Microbial network analysis indicated higher antagonism, lower modularity and shorter average path among microbes in Mn-C biofilters, which highlighted microbial differentiation and faster electron transfer. Improved functions of denitrification and Mn respiration, and the increasing genes encoding electron transfer chain, including NADH dehydrogenase, Cytc and ubiquinone, further elucidated the superiority of Mn-C com- posites. These results improved our understanding of Mn-C composites application in low-carbon wastewater treatment.
Keywords: denitrification; Electron transport; Microbial assembly; Mn-C composites; Mn-C composites increased microbial; SMX removal